Lipid and Amino Acid Pathway Metabolites Contribute to Cold Tolerance in Quercus wutaishanica - Qun Li; Yang Xu; Yan-Qun Liu; Li Qin (Metabolites, 2023)
Cold is an important environmental stress affecting the growth, productivity, and geographic distribution of tree species. Oaks are important for environmental conservation and wood supplies. Oak metabolites respond to low temperatures (LTs). In this study, the physiological and metabolic responses of two oak species to cold stress were investigated and compared. The field observations and physiological responses showed that Quercus wutaishanica was more cold-tolerant than Q. acutissima. After frost, the one-year-old twigs of Q. wutaishanica had higher survival rates, accumulated more soluble sugar and protein, and exhibited higher superoxide dismutase (SOD) activity than those of Q. acutissima. Untargeted metabolomics identified 102 and 78 differentially accumulated metabolites in Q. acutissima and Q. wutaishanica, respectively, when the leaves were subjected to LTs (4 °C for 24 h). The carbohydrate and flavonoid metabolites contributed to the cold tolerance of both oak species. Succinate, an intermediate in the citric acid cycle, was significantly inhibited by LTs, a potential energy conservation strategy. Unlike Q. acutissima, Q. wutaishanica underwent metabolic reprogramming that significantly increased the contents of phosphatidylcholine, gallic acid, oxidized glutathione, shikimate, and phenylpyruvate under LTs. Our data provide a reference for characterizing the mechanisms involved in the response of oak species to cold temperatures and enhancing the cold tolerance of forest trees.